ANALISIS DISPARITAS SPASIAL MENGGUNAKAN DYNAMIC K-MEANS CLUSTER DAN LOCATION QUOTIENT PDRB KABUPATEN CILACAP TAHUN 2014 - Rafendra Agustianda Putra; Muhammad Muhajir (Unisda Journal of Mathematics and Computer Science (UJMC), 2017)
In an effort to increase the growth an area, the government tried to advance sectors that can grow the economy in an area, one of them is gross regional domestic product (GDRP) data. A region that has an average areas with low GRDP but in the region there are areas that have very high GRDP can cause imbalance in the region. Imbalance regions is a common aspect in economic activity in a region, that is Cilacap regency. One model that is representative enough to measure the degree of imbalance of development among regions is Index Williamson (IW) and there are several methods to provide solutions in solving the problem of imbalance in Cilacap regency, among others Dynamic K-Means Clustering and Location Quotient (LQ). In this research, the results of the analysis showed IW Cilacap regency in 2014, there is imbalance but low imbalance, there is still imbalance between district due to high differences in income and sector productivity differences are striking every district in Cilacap regency. Dynamic K-Means Cluster analysis results shows the results of iteration 3 times and the number of clusters by 2 namely Cluster 1 (C1) and Cluster 2 (C2). Characteristics of C1 members advance in Sek_2, Sek_3, Sek_4, Sek_5, Sek_6, Sek_7, Sek_8, and Sek_9 while C2 members advance in Sek_1. C1 the number of members as many as 6 districts and C2 the number of members as many as 18 districts. And the result of LQ analysis shows that agriculture sector of Cilacap regency is the best potential to be developed.